Biodiversity, conservation, and environmental management in the Great Lakes Basin - Freedman, Eric; Neuzil, Mark (Routledge, Taylor & Francis Group, 2018)
This multidisciplinary book presents recent research to demonstrate the interconnected nature of the environmental challenges facing the The Great Lakes Basin in North America, which holds 20 percent of the world's fresh water, and where threats to habitats and biodiversity have economic, political, national security, and cultural implications and ramifications that cross the US-Canadian border.